Pelatihan dan Pendampingan Edukasi Laktasi Sebagai Upaya Meningkatkan Self Efficacy Ibu dalam Pemberian ASI Esklusif - Dina Mariana; Rizky Febriyanti Supriadi; Beauty Octavia Mahardany (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
The proportion of exclusive breastfeeding in Indonesia, including Mamuju Regency, remains below the national target. Interviews and observations at Bambu Public Health Center revealed that the low coverage of exclusive breastfeeding is influenced by limited knowledge and low self-confidence among breastfeeding mothers. Therefore, continuous educational interventions and mentoring focused on improving maternal self-efficacy are needed, through optimizing the role of Posyandu cadres as community-level supporters. This community service program aimed to enhance cadres’ competencies in exclusive breastfeeding education and lactation practices. The methods employed included needs assessment, provision of educational modules and media, delivery of educational materials, practical demonstrations, counseling simulations, and direct mentoring of cadres in Posyandu settings. The training results showed a significant improvement in cadres’ knowledge, with the average score increasing from 44% in the pre-test to 83.3% in the post-test, and a shift from predominantly poor knowledge to a majority in the good category. Cadres were also able to apply educational skills and sensitively correct breastfeeding practices, while providing essential motivational support to breastfeeding mothers. This improvement in cadres’ competencies is expected to contribute to increased exclusive breastfeeding coverage and improved maternal and child health indicators, highlighting the need for sustainable lactation training and mentoring programs, as well as strengthened cross-sectoral coordination.